United Kingdom : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for United Kingdom. (IMF Staff Country Reports; Country Report ;, 2016)
Considerable progress has been achieved in the post-crisis repair of the UK economy. Private-sector indebtedness has been reduced, the financial sector regulatory framework has been overhauled, the fiscal deficit has been cut in half, and the employment rate has reached a record high. With the output gap now nearly closed, growth is expected to average near its potential rate of around 2u percent over the medium term, with inflation rising slowly from its current low levels to the 2 percent target by end-2017. However, this benign baseline is subject to risks, including those related to potential shocks to global growth and asset prices, still-high levels of household debt, the elevated current account deficit, and the degree to which productivity growth will recover. Uncertainty associated with the outcome of the forthcoming referendum on EU membership could also weigh on the outlook. Continued efforts are needed to complete the post-crisis repair, promote growth, and further bolster resilience.